ผลกระทบต่อชีวิตครอบครัวของสตรีทำงานนอกบ้าน : ศึกษากรณีของอาจารย์จุฬาลงกรณ์มหาวิทยาลัย - พัชรมณี สุดรัก (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this research was to study the effect on family life of working women. By using simple random sampling method, 100 professors from Chulalongkorn University were selected to answer the questionairs. In addition other 10 professors were selected for in-depth interview. Analysis of data was conducted using SPSS program to calculate percentage, means and chi-square at the significant level of 0.05. The hypotheses of this research were as followed: 1. Older professors take care their children better than younger professors. 2. Higher educated professors take care their children better than lower educated professors. 3. Professors without administrative positions take care their children better than professors with administrative positions. 4. Professors with less children take care their children better than professors with more children. 5. Professors with higher income take care their children better than professors with lower income. The result of the research were accepted hypothesis number3 and rejected hypothesis number 1, 2, 4 and 5.